Illegality Of Income Tax Evasion In Edo State: Adopting An Automated Income Tax System As A Panacea - Aidonojie, Paul Atagamen; Nwazi, Joseph; Ugiomo, Eruteya (JURNAL LEGALITAS, 2023)
In Nigeria, the governments are mandated to collect income tax from companies and individuals respectively. However, in Edo State, it has been observed that taxpayers often tend to evade their tax liability. Although, there are several provisions of the Personal Income Tax Act and judicial pronouncement prohibiting income tax evasion, however, income tax evasion in Edo State seem to be on the increase. It is in this regard, that this study tends to embark on a hybrid method of study concerning the causes of the current increase of income tax evasion in Edo State and proposing an automated income tax as a panacea. In this regard, 304 questionnaires were distributed to respondents resident in Edo State. Descriptive and analytical methods were adopted in analyzing the data obtained. The study, therefore, found that there are several causes of income tax evasion which include; inefficient and ineffective tax administration systems, corruption and inadequate information on the assets and income of the taxpayer. Furthermore, the study also found that the adoption of an automated income tax system could serve as a major solution to rectify the above identified challenges given its relevance and prospect, although, there are some challenges concerning an automated income tax system. It is, therefore, concluded and recommended that for there to be a level playing ground in further curtailing the incidence of income tax evasion in Edo State, there is a need to intensify the automated income tax system in curing some of the defects inherent in the system.